1993
DOI: 10.1002/stem.5530110507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macrophage colony stimulating factor and granulocyte‐macrophage colony stimulating factor on osteoclastic differentiation of hematopoietic progenitor cells

Abstract: Although the hematopoietic origin of the osteoclast is generally accepted, the precise phenotype of the progenitor and the regulation of its differentiation are unclear. This study compares proliferation and differentiation of progenitors in response to macrophage colony stimulating factor (M-CSF) and granulocyte macrophage colony stimulating factor (GM-CSF). Nonadherent progenitor cells from murine long-term bone marrow cultures (LTBMC) (as a source of osteoclast progenitors) demonstrated a significant prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…However, more recent findings suggest that many of these cytokines may also affect other cell lineages. For example, G-CSF has been shown to act in synergy with IL-3 or KL to trigger very early hematopoietic progenitors into the cell cycle, and M-CSF affects placental development and osteoid cells (43)(44)(45). Of considerable interest for the present studies, Epo has been shown to augment megakaryocyte formation in the presence of aplastic serum, a known source of TPO (23,24), and to expand not only erythroid but also megakaryocyte and granulocytic progenitors in Epo-treated patients (46).…”
Section: Resultsmentioning
confidence: 99%
“…However, more recent findings suggest that many of these cytokines may also affect other cell lineages. For example, G-CSF has been shown to act in synergy with IL-3 or KL to trigger very early hematopoietic progenitors into the cell cycle, and M-CSF affects placental development and osteoid cells (43)(44)(45). Of considerable interest for the present studies, Epo has been shown to augment megakaryocyte formation in the presence of aplastic serum, a known source of TPO (23,24), and to expand not only erythroid but also megakaryocyte and granulocytic progenitors in Epo-treated patients (46).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are conflicting reports on the effects of GM-CSF on osteoclastogenesis in marrow cultures and cocultures. GM-CSF has been found to increase OCL formation in human and primate bone marrow cultures (56,57) and in some rodent cultures (58)(59)(60). On the other hand, there are many studies in murine marrow cultures and coculture systems showing that GM-CSF inhibits OCL formation (45,46,(61)(62)(63), and it has been proposed that GM-CSF inhibits OCL formation by inhibiting expression of integrin αvβ5 (64).…”
Section: Discussionmentioning
confidence: 99%
“…Here we used the purified T cells and the cell density or concentration of IL18 was not as high as in their study. Several reports also state that GM-CSF can stimulate osteoclast formation in vitro [35][36][37] and in vivo. 38 These data do not support the statement that GM-CSF mediates the inhibitory effect of IL18 on osteoclastogenesis.…”
Section: Rankl Expression In T Cells Was Discovered Bymentioning
confidence: 99%